EFFECT OF GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AND MANAGERIAL OWNERSHIP TO THE CORPORATE VALUE WITH FINANCIAL PERFORMANCE AS INTERVENING VARIABLES: CASE ON INDONESIA STOCK EXCHANGE - Ilmi, Mainatul; Kustono, Alwan Sri; Sayekti, Yosefa (International Journal of Social Science and Business, 2017)
ABSTRACTThis study aims to analyze the direct effects of good corporate governance, corporate social responsibility disclosure, and managerial ownership of corporate value, as well as to analyze the indirect effects of good corporate governance, corporate social responsibility disclosure, and managerial ownership of firm value through financial performance. The research method used is path analysis. The population in this study are all manufacturing companies listed on the BEI in 2011 - 2015, with members of the population are 146 companies. The sampling technique used purposive sampling technique, then obtained 61 companies that meet the criteria, so the total sample is 310 observations (firm - years).The result of the research shows that (1) Good corporate governance (GCG) has a significant positive effect to corporate financial performance. (2) Corporate social responsibility disclosure has positive significant effect to corporate financial performance. (3) Managerial ownership does not affect to corporate financial performance. (4) Good corporate governance (GCG) has a significant positive effect to corporate value. (5) Corporate social responsibility disclosure (CSRD) has no effect to corporate value. (6) Managerial ownership does not affect to the corporate value. (7) Financial performance has a significant positive effect to corporate value.Keywords: GCG, CSR Disclosure, managerial ownership, corporate value, financial performance.